Etiologija i ishod bakterijskih infekcija kod bolesnika s cirozom jetre : retrospektivna kohortna studija = Etiology and outcome of bacterial infections in patients with liver cirrhosis : a retrospective cohort study - Krznarić, Juraj (Array, 2020)
Introduction: Bacterial infections are a common cause of complications and decompensation in patients with liver cirrhosis. The objective of this study is to evaluate the etiology, clinical manifestations, course and outcome of bacterial infections and identify mortality predictors in patients with liver cirrhosis and sepsis. Materials/Methods: We conducted a retrospective cohort study involving 257 patients hospitalized at the University Hospital for Infectious Diseases, Zagreb over a five-year period (2011 - 2015). We analysed demographical, clinical, and microbiological data in order to identify the mortality predictors. Results: The most common clinical syndrome on admission was bacteremia of unknown origin. Chronic liver disease (CLD) was previously diagnosed in 39,2 % of patients. In 50,0 % of the cases, CLD was alcohol induced. The causative agent was isolated in 71,4 % of patients, mostly from blood cultures. Empirical therapy was corrected in 11,2 % of cases (according to microbiological findings). Median time of adequate antimicrobial therapy onset was 3 days. Complications occurred in 62,2 % of patients. Hospital stay mortality rate was 28,5 %. Delayed adequate antimicrobial therapy for a period ≥ 72 hours, invasive mechanical ventilation and acute renal failure were independently associated with fatal outcomes. Conclusion: This study describes the epidemiology and etiology of bacteriemia in liver cirrhosis patients in Croatia. Since infection is the initial sign of cirrhosis presence in our cohort, systematic screening for timely detection of CLD and prevention of complications is crucial. High rate of multiple drug resistant infections from the general population underscores the need to develop national guidelines for empirical treatment of bacterial infections in patients with liver cirrhosis.